Edukasi Bahaya Kebisingan Pada Pekerja Sektor Informal Kota Surabaya - Syahriatul Hikmiah Syahriatul; Friska Ayu; Julianti Saffana Zahra; Ridwan Khafid Alfaridzi; Merry Sunaryo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
One of the risks that can occur in the workplace is the risk of physical factors, namely noise. The physical environment is one of the important factors to play a role in the occurrence of work accidents. The role of factors in the work environment is very large with the occurrence of Occupational Safety and Health problems. To create a safe and comfortable work environment, it is necessary for workers and companies to apply Occupational Safety and Health when doing work. Noise is an unwanted sound in the work area due to production equipment or production machinery. The results of the initial survey through observation and hazard assessment using JSA and calculation using the CARL method. It was found that the highest risk assessment was the physical factor of noise. Therefore, the purpose of community service is carried out to prevent the existence of physical factor hazards, namely noise. Taking measurements using a Sound Level Meter, from the results of noise measurements that have been taken, there are work areas that exceed the Threshold Value (NAB), which gets a value of 87.92dB. It can be concluded that there is a high value of noise intensity, it should receive attention by controlling hazards that can be applied to the informal sector of PT.X, namely reducing production machine tools on the floor and moving them to the next floor, it can also be controlled by using Personal Protective Equipment (PPE), namely ear plugs when all production machine tools are operating.